Individual aggressiveness in the crab Chasmagnathus: Influence in fight outcome and modulation by serotonin and octopamine - Pedetta, Silvia (2010)
In a previous work we found that size-matched Chasmagnathus crabs establish winner-loser relationships that were stable over successive encounters but no evidence of escalation was revealed through fights. Here, we evaluated the hypothesis that size-matched fights between these crabs would be resolved according to the contestants' level of aggressiveness. Moreover, we aim at analysing the proximate roots of aggression, addressing the influence of the biogenic amines serotonin (5HT) and octopamine (OA) in crab's agonistic behaviour. To achieve these purposes, the following experiments were carried out. First, we performed successive fight encounters between the same opponents, varying the number of encounters and the interval between them, to assess the stability and progression of the winner-loser relationship. Then, we analysed dominance relationships in groups of three crabs, evaluating the emergence of linearity. Thirdly, we examined the effects of 5HT and OA injections over the fight dynamics and its result. Our findings show that contest outcome is persistent even through four encounters separated by 24. h, but a comparison between encounters does not reveal any saving in fight time or increase in the opponent disparity. Within a group of crabs, a rank-order of dominance is revealed which is reflected in their fight dynamics. Interestingly, these results would not be due to winner or loser effects, suggesting that fight outcome could be mainly explained as resulting from differences in the level of aggressiveness of each opponent. Moreover, this individual aggressiveness can be modulated in opposite directions by the biogenic amines 5HT and OA, being increased by 5HT and decreased by OA.